2011
DOI: 10.4103/0256-4947.81527
|View full text |Cite
|
Sign up to set email alerts
|

Six-year outcome of the national premarital screening and genetic counseling program for sickle cell disease and β-thalassemia in Saudi Arabia

Abstract: BACKGROUND AND OBJECTIVES:Saudi Arabia has a high prevalence of hereditary hemoglobin disorders. Data has been collected by the Saudi Premarital Screening and Genetic Counseling Program on the prevalence of sickle cell disease and β-thalassemia but the outcomes were not quantified. We used six years of premarital screening data to estimate the burden of sickle disease and β-thalassemia over the program period and to assess the frequency of at-risk marriage detection and prevention.DESIGN AND SETTING:Retrospect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
99
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 144 publications
(102 citation statements)
references
References 15 publications
3
99
0
Order By: Relevance
“…Genotype identification with education and counseling on its significance would allow persons to make informed decisions on their choice of partner and should they wish, avoid the risks of a child with sickle cell disease. 2004 -2009) indicates that out of 1.5 million marriage proposals, there had been a steadily increasing rate of marriage cancellations among at-risk couples (Memish and Saeed 2011). Among at-risk couples who continue to marry, other potential options include prenatal diagnosis and preimplantation diagnosis (Xu et al 1999).…”
Section: Prevention Of Sickle Cell Diseasementioning
confidence: 99%
“…Genotype identification with education and counseling on its significance would allow persons to make informed decisions on their choice of partner and should they wish, avoid the risks of a child with sickle cell disease. 2004 -2009) indicates that out of 1.5 million marriage proposals, there had been a steadily increasing rate of marriage cancellations among at-risk couples (Memish and Saeed 2011). Among at-risk couples who continue to marry, other potential options include prenatal diagnosis and preimplantation diagnosis (Xu et al 1999).…”
Section: Prevention Of Sickle Cell Diseasementioning
confidence: 99%
“…The advent of mandatory premarital screening programmes in both Bahrain and Saudi Arabia since 2004 will certainly reduce the number of affected births. Data from the Saudi programme for 2009 indicated that of nearly 300,000 engagements, marriage cancellations occurred in 52 % of the 1171 families receiving 'incompatible certificates' (Memish and Saeed 2011). Most published reports have occurred in communities with relatively low frequencies of the sickle cell gene and often high-technology resources offering prenatal diagnosis and termination such as the Cuban programme (Granda et al 1991) but logistical problems of follow-up and of monitoring pregnancy outcome have limited assessment of their impact.…”
Section: Discussionmentioning
confidence: 99%
“…It was concluded that the program had failed to achieve its goals although the small numbers limited the significance of this finding. Different conclusions were reached in the Kingdom of Bahrain, where voluntary premarital screening for the sickle cell gene reduced the prevalence of SS births from 2.0 to 0.9 % (Al Arrayed 2005a), and such screening became mandatory by Royal Decree in 2004 for both Bahrain (Al Arrayed 2005b) and for Saudi Arabia (Memish and Saeed 2011;Alswaidi et al 2012). These programmes will reduce the frequency of affected births but Bahrain and Saudi Arabia are Islamic societies with traditions of arranged marriage.…”
Section: Introductionmentioning
confidence: 99%
“…In Bahrain, where 16% of the population carry the HbS gene, voluntary premarital screening for the sickle cell gene reduced the prevalence of SS births from 2.0 to 0.9% (Al Arrayed 2005) and became mandatory in June 2004. Similar legislation was passed in the same year for Saudi Arabia (Alswaidi et al 2012;Memish and Saeed 2011), and the published data for 2009 show that out of nearly 300,000 marriage proposals, 1171 received 'incompatible certificates' of which, 608 (52%) marriages were cancelled. However, experience from Islamic societies with traditions of arranged marriages may not be applicable to other communities.…”
Section: Introductionmentioning
confidence: 98%